Featured Article: Modulation of fetal hemoglobin in hereditary persistence of fetal hemoglobin deletion type-2, compared to Sicilian δβ-thalassemia, by BCL11A and SOX6-targeting microRNAs - Fornari, Thais A (Exp Biol Med (Maywood), 2016)
Hereditary persistence of fetal hemoglobin deletion type-2 (HPFH-2) and Sicilian-δβ-thalassemia are conditions described as large deletions of the human β-like globin cluster, with absent β-globin chains and a compensatory variable increase in γ-globin. HPFH, in general, may be distinguished from DB-Thalassemia by higher fetal hemoglobin (HbF) levels, absence of anemia and hypochromic and microcytic erythrocytes. MicroRNAs (miRNAs) regulate a range of cellular processes including erythropoiesis and regulation of transcription factors such as the BCL11A and SOX6 genes, which are related to the regulation of γ-globin expression. In this report, a possible association among the overexpression of miRNAs and the expression of the γ-globin gene was analyzed in these two conditions. Forty-nine differentially expressed miRNAs were identified by microarrays in CD34+-derived erythroid cells of two subjects heterozygous for Sicilian-δβ-thalassemia, 2 for HPFH-2 and 3 for controls after 13 days of culture. Some of these miRNAs may participate in γ-globin gene regulation and red blood cell function. The BCL11A gene was found to be potentially targeted by 12 miRNAs that were up-regulated in HPFH-2 or in DB-Thal. A down-regulation of BCL11A gene expression in HPFH-2 was verified by quantitative polymerase chain reaction. These data suggest an important action for miRNA that may partially explain the phenotypic differences between HPFH-2 and Sicilian δβ-thalassemia and the increased expression of γ-globin in these conditions.